A Bibliometric Analysis of Service Quality in the Hospitality Industry (2014–2024) - Olakunle Shakur Olawuyi; Carina Kleynhans (Administrative Sciences)
Service quality is important for the survival of all businesses, including the hospitality business. Service quality can be measured by a model referred to as SERVQUAL, which comprises five parameters, namely, tangibility, reliability, assurance, empathy, and responsiveness. It is very important to examine publications to ascertain trends in service quality in the hospitality industry during the previous decade (2014–2024). Data were collected from the Scopus database, the article search having yielded 876 documents. The eligibility criteria were as follows: papers had to be published between 2014 and 2024, had to be written in English, and were restricted to articles, conference papers, book chapters, and review papers. The collected data were analyzed with the biblioshiny package in RStudio. The results revealed that the journal with the highest number of articles published during the period under study was Sustainability (Switzerland). Hong Kong Polytechnic was the institution with the highest number of publications vis-à-vis service quality in the hospitality industry, followed by Bina Nusantara University and Eastern Mediterranean University. It is notable that customer satisfaction featured prominently in different clusters, which emphasizes the fact that service quality is targeted at satisfying customers.